Evaluation of Oregano and α-Tocopheryl Acetate on Laying Japanese Quail Diets - E. Christaki; E. Bonos; I. Giannenas; P. Florou-Paneri (Journal of Basic & Applied Sciences, 2012)
In this experiment 108 Coturnix japonica quail, 149 days old, were randomly allocated into four equal groups with three subgroups of 9 birds each (6 females and 3 males). A commercial laying diet was fed to the control group. The remaining three groups were fed the same diet supplemented with ground oregano at 10 g/kg or 20 g/kg or additional 300 mg α-tocopheryl acetate /kg. The birds were offered feed and water ad libitum for a period of 29 days, while being kept under commercial conditions. During the whole experiment, egg production, feed consumption and mortality were recorded daily. Also, at the end of the experiment the egg weight, the weight percentages of egg yolk, albumen and shell, the egg yolk colour (using the L*a*b* colour space) were determined. Moreover, blood serum total cholesterol and triglycerides were determined. The results showed that the α-tocopheryl acetate addition did not affect any of the examined parameters. In contrast, oregano at 10 g/kg increased the a* yolk colour parameter (redness) compared to control, but did not affect the other examined parameters.